Snacking, sugar-sweetened beverage consumption and child obesity in low-income households. Issue 1 (7th May 2020) - Walsh, Christine E.; Seguin-Fowler, Rebecca; Ammerman, Alice; Hanson, Karla; Pitts Jilcott, Stephanie B.; Kolodinsky, Jane; Sitaker, Marilyn; Ennett, Susan
Abstract : Purpose: Snacking contributes to one-quarter of children's total daily energy intake in the USA, with many snack foods being nutrient-poor and energy-dense. Snacking and sugary beverage consumption have been identified as potential contributors to childhood overweight and obesity and may play a particularly important role among children from socioeconomically disadvantaged households that generally display higher rates of obesity. This exploratory study investigated associations between consumption of snack foods, sugar-sweetened beverages (SSB) and overweight and obesity in children from low-income households. Design/methodology/approach: Data from households that participated in a multi-state cost-offset (CO-CSA) community supported agriculture intervention in 2016 and 2017 ( n = 305) were analyzed. Fixed effect regression models were used to estimate associations between child monthly consumption of salty snack foods; sweet snack foods and SSBs; and child weight status, accounting for demographic characteristics. Findings: No associations were found between snack or SSB consumption and child overweight. However, household income was significantly, negatively related to all three consumption variables (Salty snacks: ß = −0.09, SE = 0.04, p = 0.02; Sweet snacks: ß = −0.10, SE = 0.04, p = 0.01; SSB: ß = −0.21, SE = 0.05, p = 0.0001). The results suggest that household income may play an important role in children's snacking and SSB behaviors among more disadvantaged households. Practical implications: Factors beyond snack food and SSB consumption should be explored to better understand childhood overweight and obesity, and to inform future obesity interventions. Originality/value: Socioeconomic disparities in childhood obesity are an ongoing policy-relevant issue within the USA and internationally. This study provides new information about child snacking behaviors in a unique, low-income population and contributes to the evidence base regarding the role household context in shaping child consumption behaviors.